Zur Rezeption Claudians: Das Wunderreich der Venus (Epithalamium de nuptiis Honori Augusti 47–98) - Simon, L. Zoltán (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
The major influence of Claudian on Neo-Latin poetry is well known but the reception of the late antique poet is still poorly studied in its details. This paper examines four typical imitations of Claudian’s splendid description of the realm of Venus. The influence of the ekphrasis will be analysed in Boccaccio’s description of the afterlife (Buccolicum carmen), in Baptista Mantuanus’ depiction of the Garden of Eden (Parthenice), in the exotic landscapes of Lorenzo Gambara’s epic poem (De navigatione Christophori Columbi), and finally in a metapoetic elegy by Girolamo Balbi.